NUMERICAL MODELLING OF SLOPE STABILITY IN OPEN PIT LIGNITE MINES: A COMPARATIVE STUDY - Deliveris, A.V.; Zevgolis, I.E.; Koukouzas, N.C. (Bulletin of the Geological Society of Greece, 2016)
Slope stability of an open pit lignite mine was studied using numerical methods (FEM and FDM), by means of three different software packages whose performance was compared and similarities - differences were identified. Plane strain analyses were performed using the shear strength reduction technique under drained conditions and Mohr-Coulomb constitutive models. Based on the results, all three programs demonstrated qualitatively a good agreement in the determination of safety factors and the kinetics of the collapse mechanisms. Small differences were observed in terms of shear strains localizations. Important differences were evident in the development of plastic (shear) and tensile failure indicators. Nevertheless, the problem under examination may be addressed satisfactorily by all three programs.